Predição de leitura, escrita e matemática no ensino fundamental por funções executivas, na linguagem oral e habilidades iniciais de linguagem escrita na educação infantil - Pazeto, Talita de Cassia Batista (2016)
The assessment of cognitive skills in preschool and the first years of elementary school has helped to understand and identify what skills are involved in learning. Among these, executive functions, oral language and early knowledge of written language have been reported as predictors of later school performance in reading, writing and mathematics. This research aimed to verify that: executive functions, verbal language, preliminary reading and writing skills, socioeconomic, biological and teacher vision -valued at preschool age- predict performance in elementary education in reading, writing and mathematics. A total of 71 children, of both genders, aged 4 and 6 years, from kindergarten 1 to the first year of a private school in São Paulo. The instruments used for the assessment of executive functions were Attention Test for Cancellation, semantic Stroop Test and Trail Making Test for Preschoolers. To evaluate oral language: Phonological Awareness Test for Oral production, Peabody’s image vocabulary test and words repetition test and Pseudoword. In assessing the initial skills of reading and writing: Task knowledge of letters and sounds and Reading and Writing Test. To evaluate school performance: Word Reading Competence Test and Pseudoword, written test under Dictation and Proof of Arithmetic. To parents was sent a file with questions about child development and family structure. To and teachers, a questionnaire on students' difficulties. The study has a longitudinal character and accompanied these children through annual assessments over three years. Imputation analysis was performed, which aims to prepare the sample for following statistics analysis. The Friedman test showed a significant number of effect on all evaluated skills. The regression tree analysis derived models of the importance of each variable for predicting the outcome variable, and Boruta analysis determined which variables were the most important for each model. Thus, according to the regression tree, phonological awareness, letter knowledge and sounds, preliminary reading and writing and vocabulary skills were predictors for later reading performance. Knowledge of letters, difficulty pointed out by the teacher, reading and preliminary writing, phonological awareness, vocabulary, the father's age, family income, inhibitory control and cognitive flexibility were the predictive skills for later writing performance. Phonological awareness, letter knowledge, reading and preliminary writing, vocabulary and difficulty pointed out by the teacher were the predictive skills for later performance in mathematics. In the face of the findings, it was possible to respond to all objectives. These results have social relevance by allowing reflect on the expansion of early identification of potential problems in these skills and preventive interventions and contribute to bringing relevant areas to be developed in early childhood education